PENGARUH METODE PEMBERIAN TUGAS TERHADAP PRESTASI BELAJAR DAN MINAT BELAJAR SISWA PADA PELAJARAN MATEMATIKA KELAS VII SMPN 6 MADIUN - Yohanes, Rudi Santoso; Arumsari, Citra Puspita (Educatio Vitae, 2015)
This study aims to determine: Is there a difference in learning achievement and interest in learning math among groups of students taught by using the method of administration tasks and groups of students taught using expository method? This study is a quasi-experimental quantitative research. The research was conducted in the first semester of the academic year 2013/2014 in SMPN 6 Madiun with a population of class VII. While the sample is VIID class as a class experiment using Learning Math Learning Provision of tasks and class VIIC as the control class with Expository learning. Data collection techniques using the test method and non test (questionnaire). Instruments used in the test method is the achievement test, while the non-test methods such as questionnaires interest. Achievement test used to determine students 'learning achievement while interest questionnaire used to determine students' interest in learning mathematics. Based on the results of research and statistical analysis diperloeh: Learning achievement and interest in learning math students who use the Learning Mathematics Learning Task Giving no better than learning achievement that use expository. Keywords: Mathematics Learning Achievement, Interest in Learning Mathematics, Mathematics Learning Method Task Giving.